Adopsi Traktor, Mesin Tanam Padi, dan Pompa Air di Lahan Sawah Pasang Surut Kabupaten Banyuasin dan Rawa Lebak Kabupaten Ogan Ilir - Hasbi Hasbi; Tri Tunggal (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Hasbi H, Tunggal T. 2019. Adoption of tractor, rice transplanter and water pump in tidal land and swamp land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 370-391. Palembang: Unsri Press. This research was aimed to determine the adoption level of agricultural technology, especially tractor, rice transplanter and water pumps of tidal farmers at Banyuasin and Ogan Ilir Regencies. This research was conducted in September 2018 until January 2019 at the Telang Mandiri (KTM) tidal rice field center, Tanjung Lago District, Banyuasin District and lowland Swamp, Pemulutan District, Ogan Ilir Regency, South Sumatra Province. This study used a descriptive method by displaying percentage values in the form of tabulations. This study used four parameters, namely farmers' perceptions of machine operation and repairing, engine performance and results obtained, machine operating costs and the level of acceptance of the machine adopted.The results showed that adoption of farmer’s perceptions of pre-harvest technology were quite high. The level of acceptance of the machines adopted in tidal land and swamp swamps in the form of tractors and water pumping machines was quite high, but the adoption of rice planting machines was very low. The level of adoption of rice planting machines on both research fields was very low, because rice planting machines were difficult to be introduced and were not suitable to be applied in swamps. The interest of farmers in the use of water pumping machines was quite high, but large-scale irrigation and drainage systems were needed so that the distribution of water was evenly distributed on each land both near the river or far from the river. The higher of farmers' interest in a technology, the faster of adoption of these technological innovations.Keywords: adoption, tractor, rice transplanter, water pump